Partnering with Rural Farm Women for Participatory Action and Ethnography - Christine Marie Eisenhauer; Carol H. Pullen EdD; Terry Nelson; Sarah A. Kumm; Jennifer L. Hunter (Rural Nurse Organization; Binghamton University, 2016)
Background: U.S. farm women experience poor access to health care and high rates of health disparities. Demographic shifts are increasing isolation and decreasing social capital for these women. Providing locally meaningful health care requires cultural-historical understanding gained through community partnership. Yet, rural farming communities present challenges to establish local-buy-in and participation for research collaboration. Purpose: This article describes the steps taken to establish an action partnership between rural, farm women and a local researcher, and outlines lessons learned from using participatory approaches to inform ethnographic research. Sample: Based in an agrarian county in the Northern Great Plains, a partnership between two farm women developed into a research study inclusive of 24 female informants (ages 22-92).   Methods: Ethnographic data (key informant interviews, focus groups, participant observation, artifact review, analytic memos, and reflective field notes) was analyzed thematically and the findings were examined reflexively to discern partnership building and participatory approaches that supported local community engagement with research. Findings: Promoters of relationship building included: 1) identifying the community gatekeepers, 2) using locally familiar language, 3) using a culturally congruent approach to recruitment, 4) accommodating seasonal farm demands, and 5) capitalizing on enthusiasm and community resolve to build partnerships for action planning. Conclusion: Local knowledge and sustained community presence are essential for rural nurses to engage in participatory action partnerships with rural farm women. Keywords: Partnership, engagement, rural farm women, participatory action, ethnography DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i1.397